Analytical Expression of the Beam-Plasma Particles Distribution Function Effect on the Electromagnetic Instability Growth Rate in Strongly Coupled Plasmas - Fatemeh Nejadtaghi; Mohammad Mahdavi; Saeid Hassan pour; Hengameh Khanzadeh; Ali Tavassoli (Iranian Journal of Astronomy and Astrophysics)
The beam-plasma particles distribution function is one of the parameters which plays an important role in the energy-traveling mechanism of the relativistic electrons generated by the laser-plasma interaction in the Inertial Confinement Fusion Plasma. This paper investigates an analytical expression of the beam-plasma particles distribution function effect such as the Kappa, Semi-relativistic Maxwellian and bi-Maxwell distributions on the Weibel electromagnetic instability growth rate in strongly coupled plasmas under the low-frequency wave condition. The obtained results show that the maximum growth rate of the beam- plasma particles with semi-Maxwell distribution function is based on the temperature anisotropy parameter, density gradient, quantum and relativistic parameters has the highest possible value compared to the other two beam-plasma particles distribution functions. Also, the bi-Maxwellian distribution function has a more stable growth rate than the Kappa and the semi-Maxwell distribution functions.